Virtual eshittiruvlarning amaliy masalalari va virtual eshittiruvlarda arbitraj qarorlarini ijroga qaratish - Barakayeva Sevinchbonu Jaxongir qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The enforcement of arbitral awards rendered after virtual hearings is a critical concern in international commercial arbitration. This study investigates the specific procedural aspects of virtual hearings that threaten the enforceability of awards under Article V of the New York Convention. A conceptual legal analysis was conducted, deconstructing the virtual hearing process into sequential stages—consent, pre-hearing testing, hearing conduct, and record-keeping. This framework was used to identify due process vulnerabilities at each stage. The procedural rules of the Tashkent International Arbitration Centre (TIAC) were analyzed as a case study of integrated risk mitigation. The analysis identifies three primary risk points, like lack of express consent, technical failures and unequal access, threatening a party’s ability to present its case and inadequate records to rebut allegations of procedural unfairness. The TIAC Rules (2021) provide a model for addressing these risks through explicit provisions for digital evidence, experimental procedures, and data confidentiality. The findings indicate that the enforceability of virtual awards is contingent on proactive and systematic procedural safeguards. Harmonizing advanced institutional rules with national arbitration laws is essential to mitigate enforcement risks and solidify the legitimacy of digital arbitration.